Pretreatment of Garlic Oil Extracts Hampers Epithelial Damage in Cell Culture Model of Peptic Ulcer Disease - Lucija Kuna; Milorad Zjalic; Tomislav Kizivat; Hrvoje Roguljic; Vjera Nincevic; Tea Omanovic Kolaric; Catherine H. Wu; Aleksandar Vcev; Martina Smolic; Robert Smolic (Medicina, 2022)
Background and Objectives: Peptic ulcer disease is a chronic disease affecting up to 10% of the world’s population. Proton pump inhibitors, such as lansoprazole are the gold standard in the treatment of ulcer disease. However, various studies have shown the effectiveness of garlic oil extracts in the treatment of ulcer disease. A cellular model can be established in the human gastric cell line by sodium taurocholate. The aim of this study was to explore the effects of garlic oil extracts pretreatment and LPZ addition in the cell culture model of peptic ulcer disease by examining oxidative stress and F-actin distribution. Materials and Methods: Evaluation was performed by determination of glutathione and prostaglandin E2 concentrations by ELISA; human gastric cell line proliferation by cell counting; expression of ATP-binding cassette, sub-family G, member 2; nuclear factor kappa B subunit 2 by RT PCR; and F-actin cytoskeleton visualization by semi-quantification of Rhodamine Phalloidin stain. Results: Our results showed significant reduction of cell damage after sodium taurocholate incubation when the gastric cells were pretreated with lansoprazole (p < 0.001) and increasing concentrations of garlic oil extracts (p < 0.001). Pretreatment with lansoprazole and different concentrations of garlic oil extracts increased prostaglandin E2 and glutathione concentrations in the cell culture model of peptic ulcer disease (p < 0.001). Positive correlation of nuclear factor kappa B subunit 2 (p < 0.01) with lansoprazole and garlic oil extracts pretreatment was seen, while ATP-binding cassette, sub-family G, member 2 expression was not changed. Treatment with sodium taurocholate as oxidative stress on F actin structure was less pronounced, although the highest concentration of garlic oil extracts led to a statistically significant increase of total amount of F-actin (p < 0.001). Conclusions: Hence, pretreatment with garlic oil extracts had gastroprotective effect in the cell model of peptic ulcer disease. However, further experiments are needed to fully elucidate the mechanism of this protective role.